Emergence of Change in Initial Teacher Training for Attention to Diversity. A Look at Management - Lozada Miranda, Rosa Janet (2021)
It was proposed to describe the needs and demands of inclusive education as a mediator in teacher practice. The analysis of two specific argumentative cases are glimpsed through two types of role: (a) teacher, (b) manager. An interview was conducted focused on a national pedagogical institute. Attention to diversity by inclusive teachers is necessary both as a guiding or teaching principle of any intercultural and inclusive institution.